Influence of Acid Mine Drainage on the soils of Nababeep, Namaqualand with reference to soil chemistry, minerals and metal mobility - Smuts, Ian Heinrich (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.